Do banks extract informational rents through collateral? - Bing Xu; Honglin Wang; Adrian van Rixtel (Bank of Finland, Institute for Economies in Transition (BOFIT), 2016)
​This paper investigates if relationship lending and bank market concentration permit informational rent extraction through collateral. We use equity IPOs as informational shocks that erode rent seeking opportunities. Using unique loan data from China, we find collateral incidence increases with relationship intensity and bank market concentration for pre-IPO loans, while these effects are moderated post-IPO. We further discover after an IPO, rent extraction is moderated for safe firms but intensified for risky firms. These results are not driven by differences or changes in financial risks. Ours is the first investigation on collateral determinants for China with loan-level data.
URN:NBN:fi:bof-201603301058
Keywords: G21; L11; 330